Epileptic seizures in anaplastic gangliogliomas. (4th March 2017) - Zanello, Marc; Pagès, Mélanie; Roux, Alexandre; Peeters, Sophie; Dezamis, Edouard; Puget, Stéphanie; Devaux, Bertrand; Sainte-Rose, Christian; Zerah, Michel; Louvel, Guillaume; Dumont, Sarah N.; Meder, Jean-François; et al.
Abstract: Aim: Prevalence and predictors of epileptic seizures are unknown in the malignant variant of ganglioglioma. Methods: In a retrospective exploratory dataset of 18 supratentorial anaplastic World Health Organization grade III gangliogliomas, we studied: (i) the prevalence and predictors of epileptic seizures at diagnosis; (ii) the evolution of seizures during tumor evolution; (iii) seizure control rates and predictors of epilepsy control after oncological treatments. Results: Epileptic seizures prevalence progresses throughout the natural course of anaplastic gangliogliomas: 44% at imaging discovery, 67% at histopathological diagnosis, 69% following oncological treatment, 86% at tumor progression, and 100% at the end-of-life phase. The medical control of seizures and their refractory status worsened during the tumor's natural course: 25% of uncontrolled seizures at histopathological diagnosis, 40% following oncological treatment, 45.5% at tumor progression, and 45.5% at the end-of-life phase. Predictors of seizures at diagnosis appeared related to the tumor location (i.e. temporal and/or cortical involvement). Prognostic parameters of seizure control after first-line oncological treatment were temporal tumor location, eosinophilic granular bodies, TP53 mutation, and extent of resection. Prognostic parameters of seizure control at tumor progression were a history of epileptic seizures at diagnosis, seizure control after first-line oncological treatment, eosinophilic granular bodies, and TP53 mutation. Conclusion: Epileptic seizures are frequently observed in anaplastic gangliogliomas and both prevalence and medically refractory status worsen during the tumor's natural course. Both oncological and antiepileptic treatments should be employed to improve the control of epileptic seizures and the quality of life of patients harboring an anaplastic ganglioglioma.